Peran Mikroba Dekomposer Selulolitik dari Sarang Rayap dalam Menurunkan Kandungan Selulosa Limbah Pertanian Berselulosa Tinggi - Mieke Rochimi Setiawati; Nizar Ulfah; Pujawati Suryatmana; Reginawanti Hindersah (Fakultas Pertanian Universitas Padjadjaran, 2019)
Agricultural waste is rich in cellulosic material that is difficult to degrade but can be decomposed by cellulase enzymes. Cellulosic material is an organic component abundantly in nature in the form of cellulose and hemicellulose polymer. Utilization of microbes in the process of waste bioconversion can be done to get added value from the waste material into other products such as organic fertilizer. Cellulase-producing microbes can be isolated from various sources, one of which is from termite nests. The use of microbes from termite nests as decomposers for composting high-yielding agricultural waste was carried out in this study. Cellulolytic microbial isolates (combination of bacteria and fungi and without decomposers) were applied to agricultural wastes high in cellulose content: rice straw, bagasse, and oil palm empty fruit bunches. Randomized Block Design was applied and each treatment was and repeated 3 times. The composting process was carried out for 1 month indoors. The results showed that cellulolytic microbial consortium obtained from termite nests reduced the compost cellulose content of bagasse agricultural waste in one month. Whereas rice straw and oil palm empty fruit bunches showed a tendency to decrease cellulose content because cellulose degradation by decomposer microbes still continues after one month of incubation.